PROBLEMS IN OPERATING AN INTERNATIONAL DIGITAL ASSET BUSINESS OPERATIORS COMPARE THAI LAW WITH THE REPUBLIC OF SINGAPORE - Narapongsathorn, Tuchpapol; Wongwitit, Sumalee (Academic Journal Phranakhon Rajabhat University, 2024)
This article aims to examine the challenges in remedying the damages faced by investors from international digital asset fundraising by business operators. The research employs a qualitative methodology, utilizing document analysis and comparing Thai law with that of the Republic of Singapore concerning the regulation and oversight of digital asset businesses. It focuses on the responsibilities and liabilities of international digital asset business operators and the measures available for compensating investors affected by their fundraising activities. The research uncovers that Thai law lacks comprehensive coverage regarding discretionary powers and regulatory oversight of digital asset businesses. It also lacks clear guidelines on liability issues, leading to delays in addressing investor damages with no established compensation fund or plan. The study recommends defining digital asset characteristics based on their intended use to ensure clear supervision. Unauthorized individuals, especially influencers who influence online user decisions, should be prohibited from advertising. Stricter penalties should be enforced for violations, and a compensation fund and plan for affected investors must be established.